Analysis Of Factors Affecting Nurse Performance At Moh Ridwan Meuraksa Hospital, Jakarta - Ardhestiro Harnindyo Putro; Alih Germas Kodyat; Laila Ulfa; Ignatius Erik Sapta Yanuar (Journal of Ageing And Family, 2024)
Nurse performance plays a crucial role in improving hospital service quality. Level II Hospital Moh Ridwan Meuraksa faces challenges in ensuring optimal nurse performance, including aspects of leadership, job satisfaction, organizational commitment, and recognition and rewards. This study aims to analyze the influence of transformational leadership style, job satisfaction, organizational commitment, and recognition and rewards on nurse performance at the hospital. The method used is a quantitative approach with a cross-sectional design. Data were collected through a questionnaire completed by 180 respondents and analyzed using chi-square tests and multiple logistic regression. The results showed that job satisfaction (p = 0.000, OR = 5.57) and recognition (p = 0.000, OR = 6.00) had a significant relationship with nursing performance. Meanwhile, leadership style (p = 0.006, OR = 2.67) and organizational commitment (p = 0.000, OR = 4.76) were also significantly related but were not included in the final model. In the multivariate analysis, rewards (OR = 7.270) and job satisfaction (OR = 6.78) were found to be significant, with rewards as the dominant factor. The Hosmer and Lemeshow test indicated good model fit (p = 0.702). In conclusion, nurse performance is significantly influenced by rewards and job satisfaction. Therefore, hospitals are advised to optimize performance-based reward systems and improve job satisfaction to enhance the quality of healthcare services.